The impact of University reopenings on COVID-19 cases in Scotland - Héctor Rufrancos; Mirko Moro; Eva Moore (Global Labor Organization (GLO), 2021)
This paper estimates the impact of University reopenings in Scotland in Autumn 2020 on COVID-19 cases in Scottish neighbourhoods. We geolocate all student halls in Scotland, and merge this data with neighbourhood-level case data. We employ a local differences-indi fferences strategy and tackle two research questions. First, we ask what was the impact of the start of semester on cases in the student neighbourhoods? Next, we turn our attention to the spillover of cases in the nearby communities to student neighbourhoods. University semester start dates in Scotland are staggered over the month of September, and we deal with this by focusing on each start cluster, as well as implementing the Callaway and Sant'Anna (2020) estimator. We find a substantial and persistent increase in cases in areas containing halls and evidence of persistent spillovers. These effects are linked to the group of Universities that started on 14th September, which include large Universities located in the major urban areas. The cases began to rise on 21st September, with 100 extra cases per 100,000 per day, and peaked a week later with 400 additional cases per 100,000 per day, after which they started declining, but persist until the Autumn tightening of coronavirus restrictions bit in November, two months after the restrictions were enacted. Our results invite a re-think of how close contact activities may safely resume.
Keywords: I10; I18; I28; 330; Covid Economics; University reopenings; cases; Public Health